(untitled) (Cambridge, 2001)
Heretofore, the study of the Middle East has focused almost exclusively on Islam and on the regime, especially on its non-democratic aspects. It has done so at the expense of accounting fully for the forces of skepticism, liberty, and creativity that struggle against Islamic conformism and state hegemony. This volume examines how Middle Eastern peoples in the 19th and 20th centuries lived and flourished while trying to shape their political and religious surroundings outside the formal structures of established religion and the state.
Keywords: Islam and state,Islam and politics,Đạo Hồi và Nhà nước,Đạo Hồi và chính trị; Islamic countries,Islamic countries,Quốc gia đạo Hồi,Quốc gia đạo Hồi